Trends and Predictors of Syphilis Prevalence in the General Population: Global Pooled Analyses of 1103 Prevalence Measures Including 136 Million Syphilis Tests. (9th November 2017) - Smolak, Alex; Rowley, Jane; Nagelkerke, Nico; Kassebaum, Nicholas J; Chico, R Matthew; Korenromp, Eline L; Abu-Raddad, Laith J
Abstract : Syphilis prevalence has been declining in every region by several percentage points per year. Nevertheless, the prevalence by region continued to vary, from as little as 0.1% in the European Region to as high as 3% in the African Region. Abstract: Background: This study assessed levels, trends, and associations of observed syphilis prevalence in the general adult population using global pooled analyses. Methods: A standardized database of syphilis prevalence was compiled by pooling systematically gathered data. Random-effects meta-analyses and meta-regressions were conducted using data from the period 1990–2016 to estimate pooled measures and assess predictors and trends. Countries were classified by World Health Organization region. Sensitivity analyses were conducted. Results: The database included 1103 prevalence measures from 136 million syphilis tests across 154 countries (85% from women in antenatal care). Global pooled mean prevalence (weighted by region population size) was 1.11% (95% confidence interval [CI], .99–1.22). Prevalence predictors were region, diagnostic assay, sample size, and calendar year interacting with region. Compared to the African Region, the adjusted odds ratio (AOR) was 0.42 (95% CI, .33–.54) for the Region of the Americas, 0.13 (95% CI, .09–.19) for the Eastern Mediterranean Region, 0.05 (95% CI, .03–.07) for the European Region, 0.21 (95% CI, .16–.28) for the South-East Asia Region, and 0.41 (95% CI, .32–.53) for the Western Pacific Region. Treponema pallidum hemagglutination assay (TPHA) only or rapid plasma reagin (RPR) only, compared with dual RPR/TPHA diagnosis, produced higher prevalence (AOR >1.26), as did smaller sample-size studies (<500 persons) (AOR >2.16). Prevalence declined in all regions; the annual AORs ranged from 0.84 (95% CI, .79–.90) in the Eastern Mediterranean to 0.97 (95% CI, .97–1.01) in the Western Pacific. The pooled mean male-to-female prevalence ratio was 1.00 (95% CI, .89–1.13). Sensitivity analyses confirmed robustness of results. Conclusions: Syphilis prevalence has declined globally over the past 3 decades. Large differences in prevalence persist among regions, with the African Region consistently the most affected.